A Reclusive Foreign Body in the Airway: A Case Report and a Literature Review - Ajay Philip; V. Rajan Sundaresan; Philip George; Satyabrata Dash; Regi Thomas; Anand Job; V. K. Anand (Case Reports in Otolaryngology)
A foreign body in the larynx is an airway emergency that requires urgent evaluation and treatment. Irregular foreign bodies tend to orient in a sagittal plane and may produce only partial obstruction, allowing adequate air movement, hence making them undetectable for a long period of time. We report a case of a laryngotracheal foreign body that remained reclusive for 9 years.